'Aligning activities': coordination, boundary activities, and agenda setting in interdisciplinary research. (9th January 2018) - Bernard de Raymond, Antoine
Abstract: This article examines the role of intermediary agencies in the coordination of interdisciplinary research programmes, basing on the case of the UK Global Food Security programme. Interpreting food security as a 'wicked problem', it shows that coordination is not so much a question of monitoring the implementation of a predefined research programme, as one of creating and maintaining research groups whilst at the same time ensuring a coextensive redefinition of a programme's objectives. Management of the competition between and the prioritisation of approaches of a complex problem require programme coordinators to develop activities that make it possible to manage the abundance of both existing knowledge and the issues to be examined. Finally, such coordination has an external impact, as part of a process of bringing food security onto the agenda in competitive arenas for global public policies.